Code Switching in English Teaching Learning Processes of English as a Foreign Language - Laela Markhamah; Absharini Kardena (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This research was done because code-switching was a phenomenon that exists in teaching-learning English as a foreign language, where the teachers used more than one language to communicate including in the teaching-learning processes of English as the foreign language at SMAN 2 Bukittinggi. The design of this research was descriptive qualitative research. The instruments of this research were interview for analyzing the functions of teacher’s code-switching and the observation for analyzing the types and the frequencies of teacher’s code-switching. The population of the research was all the English teaches. The sample was one of the English teacher eleventh’s grade at SMAN 2 Bukittinggi taken by randomly technique where the teacher was no-native of English speaker. The result of the research showed that in the three types of teacher’scode-switching they were 139 times inter sentential switching, 256 times intra sentential switching, 79 times tag switching. Besides, in the functions of code-switching were in 115 times of total frequencies by different modified of the functions were in classroom management (24,35%), inserting humor (2,60%), clarification of information (47,83%), increasing students’ comprehension (18,26%), and interpreting the lesson (6,96%). Then, distributions of teachers’ languages were 474 times or frequencies, the languages distribution were Pure English (44, 30%), Indonesian (29, 96%), and local language (25, 74%). Thus, this research found about three factors of teacher’s code switching that were the types of codeswitching, the functions of code switching, and the frequencies of teacher’s code-switching.